Total Quality Management, Organizational Culture, and Job Satisfaction as Determinants of Teacher Performance - Evi Zahara; Saiful Bahri; Rezeki Muamar (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The performance of teachers is a crucial factor influencing educational quality, especially in elementary schools where core skills are developed. This research examines the impact of Total Quality Management (TQM), organizational culture, and work satisfaction on the performance of elementary school educators in Trienggadeng District, Pidie Jaya Regency, Indonesia. This research, rooted in organizational behaviour theory, employs a quantitative explanatory methodology. Data were gathered from primary school educators using standardized questionnaires assessing TQM implementation, organizational culture, job satisfaction, and teacher performance. The data were studied by path analysis to investigate both direct and concurrent correlations among variables. The results indicate that Total Quality Management and organizational culture significantly enhance teachers' job happiness. Moreover, Total Quality Management, organizational culture, and job happiness each have a substantial direct impact on teacher performance. The three independent factors collectively account for a significant amount of the variance in teacher performance, suggesting that quality-oriented management practices, a supportive corporate culture, and satisfied work-related requirements boost instructional efficacy. his study enhances the domain of educational management by presenting empirical evidence of a comprehensive model that connects managerial, cultural, and psychological aspects to teacher performance in primary education. The findings emphasize the necessity of reinforcing continuous quality improvement, fostering a positive school culture, and augmenting teacher job satisfaction as strategic measures to enhance educational outcomes.